Effects of magnetic field pretreatment and chloride salt stress on physio-biochemical changes and γ-aminobutyric acid accumulation in germinated brown rice - Ying Zhu; Shengqi Tan; Chong Xie; Dandan Li; Pei Wang; Runqiang Yang (Food Materials Research)
Germinated brown rice is a staple food with high nutritional value and market prospects. Gamma-Aminobutyric Acid (GABA), abundantly present in germinated brown rice, has attracted significant attention due to its multiple active functions on the human body. This study aimed to enrich GABA in germinated brown rice by using static magnetic field pretreatment and NaCl, CaCl2 and KCl stress. After selecting Nanjing9108, which had the highest GABA content among the nine cultivars, a single-factor experiment was conducted and optimized the pretreatment condition as 10 mT static magnetic field for 40 min. Under this condition, the GABA content in brown rice germinated for 36 h was 66.35 mg/100 g, which was 13.88% higher than the control group. Simultaneously, the germination rate and early growth of germinated brown rice were also promoted. The optimal combination of culture medium for GABA enrichment obtained by response surface experimental design was NaCl 37.23 mmol/L, CaCl2 4.71 mmol/L, and KCl 5.75 mmol/L, with a GABA content of 69.783 mg/100 g. Under this condition, the changes in nutrients and the expression of glutamic acid decarboxylase (GAD) and GABA transaminase (GABA-T) related genes during the 0-48 h germination process of brown rice were studied. The relative expression of GAD was promoted and the relative expression of GABA-T was inhibited, resulting in the accumulation of GABA. This indicates that the combination of static magnetic field and salt treatment is an effective method to increase the GABA content in germinated brown rice.